G-3 EFFECT OF AGING TIME ON CRYSTALLINE STRUCTURE EVOLUATION OF TiO_2 NANOPARTICLES(Session: Titanium Oxide) - Thammarat Panyathanmaporn; Angkhana Jaroenworaluck; Sitthisuntorn Supothina; Kannikar Juengsuwattananon; Supatra Jinawath; Tawan Sooknoi; Sittinun Tawkaew (My University, 2006)
The present study shows that the aging time of sol-gel process used to prepare the TiO_2 powder had pronounced effect on anatase-rutile phase transformation and the crystalline size. The complete rutile phase transformation was observed within 40 days of aging. The results of XRD and TEM were presented to explain this phenomenon.
Keywords: Rutile; Titanium oxide; TiO2 Photocatalysis and Solar Cells